Analisis Buku Matematika Siswa Kelas V SD ditinjau dari Unsur Science, Technology, Engineering and Mathematics - Dalifa; Agusdianita, Neza; Kurniawati, Ike (Jurnal PGSD, 2023)
STEM is an approach that combines four scientific disciplines namely, Science, Technology, Engineering and Mathematics which collaborate in helping students to collect, analyze and solve problems be able to understand the relationship between a problem and other problems in one learning process. This study aims to analyze the Mathematics textbooks of fifth grade Elementary School Students in terms of the Elements of Science, Technology, Engineering and Mathematics. This research is a descriptive qualitative research. The subject of this study was Mathematics textbook fifth grade 2013 curriculum. The results showed that in each material at KD 3.5 and 3.6 in terms of the STEM approach were (1) for elements of science (Science) emergence the indicator of 50% in KD 3.5 is 15. while in KD 3.6 there is no occurrence. (2) for Technology elements, the occurrence of 75% indicator in KD 3.5 is 31. Meanwhile, in KD 3.6, the occurrence of 50% indicator in KD 3.5 is 6. (3) for Engineering elements, the occurrence of indicator is 80% in KD 3.5 79. Meanwhile, in KD 3.6 the occurrence of 80% indicator in KD 3.6 was 34. (4) for Mathematics elements, the occurrence of 100% indicator in KD 3.5 was 183. Meanwhile in KD 3.6 the occurrence of 100% indicator in KD 3.6 was 28.